Shai Feraro and Ethan Doyle White (eds.), Magic and Witchery in the Modern West: Celebrating the Twentieth Anniversary of 'Triumph of the Moon'. (8th November 2021) - Hale, Amy
Abstract : Shai Feraro and Ethan Doyle White (eds.), Magic and Witchery in the Modern West: Celebrating the Twentieth Anniversary of 'Triumph of the Moon' (London: Palgrave Macmillan, 2019), xiii + 259 pp., $119.99 (hbk), ISBN: 9783030155490.